METHODOLOGY OF TEACHING DRAWING WITH OTHER SUBJECTS BASED ON AN INTEGRATIVE APPROACH (Web of Teachers: Inderscience Research, 2025)
This article describes the methodology of teaching drawing with other subjects based on an integrative approach.